Pengaruh Kepemimpinan, Budaya Organisasi, dan Motivasi Kerja Terhadap Kinerja Karyawan - Eka Wulan Prasetia (EKONOMI DAN BISNIS DIGITAL, 2022)
Purpose of this article: This study aims to test the effect of leadership, organizational culture and work’s motivation to employee performance. Methodology: Research methodology is quantitative methodology by distributing questionnaires to employees. Results: Thisresearch is show positive result and significant partially from variable effect of leaderhip,organizational culture, work’s motivation, and employees performance. Keywords: Leadership, Organizational Culture, Work’s Motivation.